2001
DOI: 10.1046/j.1471-4159.2001.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate of AMP, IMP, GMP and XMP in the cytosol of rat brain: an experimental and theoretical analysis

Abstract: A systematic study of the metabolic fate of AMP, IMP, GMP and XMP (NMP) in the presence of cytosol from rat brain is here presented; the kinetics of both disappearance of NMP, and appearance of their degradation products was followed by HPLC. In the absence of ATP, AMP was preferentially degraded to adenosine with concomitant appearance of inosine and hypoxanthine. In the presence of ATP, AMP was preferentially degraded via IMP. The nucleosides generated in the course of the reactions are further degraded, alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…The velocity equations considered for E 1 , E 3 , E 4 , E 5 , E 6 and E 7 were as in Torrecilla et al . [3]; those for E 2 and E 8 are indicated in the text and Table 3.…”
Section: Max Km and Ki Values Of Enzymes Involved In The Adenine Amentioning
confidence: 99%
See 3 more Smart Citations
“…The velocity equations considered for E 1 , E 3 , E 4 , E 5 , E 6 and E 7 were as in Torrecilla et al . [3]; those for E 2 and E 8 are indicated in the text and Table 3.…”
Section: Max Km and Ki Values Of Enzymes Involved In The Adenine Amentioning
confidence: 99%
“…Aliquots were taken at the indicated times and analyzed by HPLC. In (B) application of the theoretical model was performed with the mathematica ‐3.0 program, as described in the text and in [3]. The V ‐values, from control cells, and the kinetic parameters described in Table 3 were used.…”
Section: Max Km and Ki Values Of Enzymes Involved In The Adenine Amentioning
confidence: 99%
See 2 more Smart Citations
“…In rat brain, it was observed that the formation of IMP in the intracellular space is predominant under normoxic or moderate hypoxic conditions, whereas the formation of adenosine prevails when ATP levels fall to anoxic values. [14,15] The accumulation of IMP is also predominant in skeletal muscle under hypoxia [16] and in flying muscle of locusts under anoxia. [17] Unlike the mammals, the animals adapted to hypoxia=anoxia transient are able to withstand without O 2 for long periods.…”
Section: Introductionmentioning
confidence: 99%